Risk Management in Mergers and Acquisitions - Dmitry O. Verdiev (Vestnik MGIMO-Universiteta, 2015)
M&A statistics show that less than a third of newly merged companies has realized their planned synergistic effects and increased shareholder value. According to the author, such disgusting situation is due to improper planning and failure of corporate management to understand the importance of risk management in M&A. Lack of practice in identification, evaluation, mitigation and regular monitoring of risks leads to the situation when many companies merge despite the fact that the merger bears substantial risks. Corporate management fails to include risk mitigation expenses in merger costs. In many cases, risk mitigation expenses may be so substantive that the merger loses its attractiveness. Only few companies implement risk management methodology while planning M&A activity. This methodology may anticipate and minimize the consequences of various risk factors that negatively influence integration process. The article suggests an implementation of risk management best practice. This risk management best practice may act as an effective tool of successful realization of synergistic effects in M&A and may be helpful in increasing shareholder value in post-merger period. Risk management is conducted throughout the stages of merger and includes identification, analysis, assessment, management and monitoring of risks. Implementation of risk management at early stages of merger planning significantly decreases uncertainty in relation to achievement of financial and operational goals of newly merged company. The article provides with typical M&A risk matrix that may be adapted for specific M&A project. Risk matrix includes a register of risks sorted by stages of M&A deal, quality assessment of their probability, influence and impact on merger as well as risk mitigation methods.